अर्थवत् प्रमाणम् - Mishra, Bhavani Prasad (Haimaprabha, 2026)
The word philosophy seems to be used as a means of knowledge of reality, derived from the word seen and known, which means the essence of reality. In order to determine matter, philosophies accept the number and form of evidence to support their own opinions according to theory and to corrupt the ultimate. Evidence is purposeful and meaningful. The meaning of proof is that which is measured, or that which the proof acquires knowledge relating to, or that which is the subject of proof, such as pleasure and pain. In this graph, the objective is to raise the problem of how evidence becomes meaningful and to solve it as a means of authenticity. Since philosophy of law is a science of evidence, only the direction of philosophy of law has achieved the meaningfulness of evidence in this research. In this qualitative co-purposeful research based on texts, the original texts of the philosophy of law and other texts related to the evidence of the philosophy of law have been compiled as primary and secondary materials respectively. A description of those materials has been prepared and concluded. There is evidence in the form of a means of knowledge. This evidence, in the philosophy of law, is of four kinds: direct, inferential, metaphorical, and sound. Evidence produces knowledge related to meaning by flooding or order. In the philosophy of justice, only form and taste of the senses such as the eye are expressed by the term meaning, but pleasure and pain arising from the proximity of the senses such as form and taste are mainly expressed here by the term meaning, since they are directly perceived by living beings. By that knowledge, if the proof is able to engage in the desired form, or to refrain from the adverse, then the meaningfulness of the proof is proved. And if the proximity of the sense objects is the proof, then knowledge is the fruit, and when knowledge is the proof, then the intellect of neglect of the cause of loss is the fruit. In this way, the conclusion is prescribed here by establishing the meaningfulness of the evidence.